Designing interactive web sites - Mohler, James L; Duf, Jon M (Cambridge Delman Thomson Learning, 1999)
This comprehensive book provides an in-depth look at the fundamentals of effective web-design and site construction.The novice web designers learns the process of creating an interactive web-site step by step,using real world examples along the way.Users
Keywords: Interactive multimedia; Websites-Design; Web publishing